The Urgency of Reforming Marriage Laws and Compilation of Islamic Law Entering the 5.0 Era - Mu'in, Fathul; ., Khairudin; Santoso, Rudi; ., Triono; Hasan, Zainudin (KnE Social Sciences, 2024)
Marriage laws and the compilation of Islamic Law in Indonesia have a very important role because they are a reference for the people and judges in religious courts. However, several rules in the two regulations are no longer in accordance with the times, which are currently entering the 5.0 era. This research includes library research whose data sources come from laws and scientific articles. This study concludes that the rapid development of times and technology has an impact on Islamic law. Therefore, reforms are needed that can respond actively to changes that occur in society, so that the relevance of Islamic law is maintained. Keywords: update, marriage law, compilation of Islamic Law, 5.0